A pictorial review on clinicopathologic and radiologic features of duodenal gastrointestinal stromal tumors - Jung, Haerang (Diagn Interv Radiol, 2020)
Duodenal gastrointestinal stromal tumors (GISTs) are rare, and studies on their management are not sufficient. Owing to the complex anatomy of the duodenum and pancreatic head, GISTs can be misdiagnosed as pancreatic head tumors. Surgical resection is the first treatment for localized duodenal GISTs; thus, noninvasive imaging is important for the diagnosis and treatment of GISTs. Computed tomography, magnetic resonance imaging and endoscopic ultrasonography findings can be helpful for the diagnosis of duodenal GISTs and can help differentiate GISTs from other adjacent tumors.